Perancangan Dan Implementasi Sistem Pengamanan Pada Sepeda Motor Menggunakan Internet Berbasis Raspberry-pi - Muhammad Aditya Taufik; Leanna Vidya Yovita; Ramdhan Nugraha (eProceedings of Engineering, 2016)
Security system on motorcycle today are still very less attention. At the same time it needs a Security system for vehicles, especially motorcycles. By using raspberry-pi would be made a security system for a motorcycle that is capable of controlling a motorcycle with the Internet as the interface. With this system the user can controlled the system. Communicate with system with two-way communication using a ‘telegram’ chatting application, and tracking location using geolocation technology. Keywords—Raspberry-Pi, Internet, Telegram, Geolocation